Endangered edible orchids and vulnerable gatherers in the context of HIV/AIDS in the Southern Highlands of Tanzania - Challe, Joyce FX (BioMed Central, 2009)
BACKGROUND: Tanzania is a wild orchid biodiversity hotspot and has a high prevalence of HIV/AIDS. The wild orchids in the study are endemic and protected by the Convention on International Trade in Endangered Species. Every year, however, between 2.2 and 4.1 million orchid plants consumed in Zambia are estimated as originating from Tanzania. This research examines the differences between HIV/AIDS wild edible orchid gatherers and non-HIV/AIDS gatherers with regards to the frequency of gathering, salience in naming the various orchids, gathering knowledge acquisition and perceptions regarding the current state of abundance of the edible species. METHODS: Data was collected through interviews with 224 individuals in the Makete District of Tanzania close to the boarder of Zambia. Free-listings were conducted and Sutrup's Cultural Significance Index (CSI) constructed. The independent t-test was used to compare the differences in gathering frequencies between affected and non-affected gatherers. A multiple comparison of the 4 subgroups (affected adults and children, and non-affected adults and children) in gathering frequencies was done with a one way ANOVA test and its post hoc test. To examine the difference between affected and non-affected gatherers difference in source of gathering knowledge, a chi square test was run. RESULTS: Forty two vernacular names of gathered orchid species were mentioned corresponding to 7 botanical species belongs to genera Disa, Satyrium, Habenaria, Eulophia and Roeperocharis. Ninety-seven percent of HIV/AIDS affected households state that orchid gathering is their primary economic activity compared to non-HIV/AIDS affected households at 9.7 percent. The HIV/AIDS affected gathered significantly more often than the non-affected. AIDS orphans, however, gathered most frequently. Gatherers perceive a decreasing trend of abundance of 6 of the 7 species. Gathering activities were mainly performed in age based peer groups. The results revealed a significant difference between affected and non-affected individuals in terms of their source of gathering knowledge. CONCLUSIONS: HIV/AIDS is related to increased reliance on the natural environment. This appears even more so for the most vulnerable, the AIDS orphaned children followed by HIV/AIDS widows.